2014
DOI: 10.3402/jmahp.v2.22813
|View full text |Cite
|
Sign up to set email alerts
|

Drug reformulations and repositioning in the pharmaceutical industry and their impact on market access: regulatory implications

Abstract: BackgroundRepurposing has become a mainstream strategy in drug development, but it faces multiple challenges, amongst them the increasing and ever changing regulatory framework. This is the second study of a series of three-part publication project with the ultimate goal of understanding the market access rationale and conditions attributed to drug repurposing in the United States and in Europe. The aim of the current study to evaluate the regulatory path associated with each type of repurposing strategy accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…After its initial approval for metastatic colorectal cancer (mCRC) in January 2005, nine more indications were launched over the following seven-year timespan; four in the year 2007 (breast cancer, non-small cell lung cancer, renal cell cancer and a different treatment regimen for mCRC), one in 2009 (a different treatment regimen for breast cancer), three in 2011 (ovarian, fallopian tube or peritoneal cancer and two different treatment regimens for breast cancer) and one in 2012 (different stage of ovarian, fallopian tube or peritoneal cancer). [26] The work of Murteira et al [25] revealed that such a strategy is commonly practised. The majority of repositioning cases 2 2

Repositioning is defined as the process of finding a new therapeutic use for an already known drug.

analysed in this study, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…After its initial approval for metastatic colorectal cancer (mCRC) in January 2005, nine more indications were launched over the following seven-year timespan; four in the year 2007 (breast cancer, non-small cell lung cancer, renal cell cancer and a different treatment regimen for mCRC), one in 2009 (a different treatment regimen for breast cancer), three in 2011 (ovarian, fallopian tube or peritoneal cancer and two different treatment regimens for breast cancer) and one in 2012 (different stage of ovarian, fallopian tube or peritoneal cancer). [26] The work of Murteira et al [25] revealed that such a strategy is commonly practised. The majority of repositioning cases 2 2

Repositioning is defined as the process of finding a new therapeutic use for an already known drug.

analysed in this study, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In certain cases, medicine developers may choose to reformulate, protect (e.g., through second medical use patents) and rebrand an established medicinal product to create sufficient legal and strategic protection from generic competitors (Smith, 2011;Novac, 2013;Dilly and Morris, 2017). For developers other than the original marketing authorization holder, a new full marketing authorization application may even offer a 10-year period of data and marketing protection for the repurposed product (Murteira et al, 2014a).…”
Section: Regulatory Incentives For Marketing Authorizationmentioning
confidence: 99%
“…Repurposing of existing medicines can be particularly useful in areas with high unmet needs, for example to treat patients with rare diseases (Norman, 2013;Murteira et al, 2014a). In fact, studies have shown that about one in five orphan medicinal products are established medicines that were repurposed for a new indication (Davies et al, 2017).…”
Section: Regulatory Incentives For Marketing Authorizationmentioning
confidence: 99%
“…This refers to the exploitation of known drugs for new indications [ 7 ]. Repurposing receives attention in both the United States and Europe, although differences exist between both continents with respect to policies for repurposing of medicinal products [ 8 ]. Several initiatives have been created to identify possible targets for drug repositioning [ 7 ].…”
Section: Introductionmentioning
confidence: 99%